Oczekiwania i doświadczenia wsparcia rodziców dzieci z niepełnosprawnością - Buchnat, Marzena (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2021)
Most parents of children with disabilities still do not know what support they can expect in the situation in which they have found themselves, and where and to whom they can turn for such support. Knowledge on this subject by medical, educational and local government employees is non-complex and does not create a coherent system, and therefore does not meet the expectations and needs of the parents. Assessment of the support obtained by individual groups, as well as access to suport systems and legal, financial and psychological assistance in the rehabilitation of a child in the organization of free time, is very diverse, which proves the ineffective functioning of information on such support and assistance systems. The aim of the conducted research was to what support was given to parents of children with disabilities and whether it is relevant to their needs and expectations. The research used a quantitative and qualitative strategy. The research used the method of diagnostic survey was used, in which a questionnaire and a focus group interview were conducted. The results show that according to the parents of children with disabilities still do not receive adequate support in Poland in the situation in which they have found themselves. A coherent system should be created for the management of an integrated package of services to support families raising a child (children) with disabilities. This system, based on medical, educational and territorial employees, should provide comprehensive and effective access to information about the forms of support and assistance available to such families.